Microcrystal bead high-efficiency water-permeable composite brick and preparation method thereof
By using the combination of modified polyurethane and epoxy nano-silica in permeable bricks, the compressive resistance and water permeability of microcrystalline beads are improved, and the compressive strength of existing white cement-based permeable bricks is solved. The problem of easy blockage achieves better durability and flexural strength.
Patent Information
- Application Number
- CN202411259508.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-27
AI Technical Summary
The existing white cement-based permeable bricks have a large permeability coefficient but low compressive strength, which is easily blocked by silt and sand, have poor water permeability and poor flexural strength.
Microcrystalline beads are used to efficient permeable composite bricks, including the base layer and the surface layer. The base layer is composed of ceramic shale particles, ceramic fine powder, white cement and reinforcement. Modified polyurethane, epoxy nanosilica and quartz powder are used in the surface layer. , mechanical properties and durability are improved by the ring-opening reaction of modified polyurethane with epoxy nanosilica.
It achieves better compressive resistance and water permeability, while avoiding the bleaching of alkaline and whitening, and improving the flexural strength and durability of composite bricks.
Smart Images

Figure BDA0005035100990000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite bricks, in particular to microcrystalline bead high-efficiency water-permeable composite bricks and a preparation method thereof. Background Art
[0002] The current permeable bricks basically belong to the coarse aggregate concrete series with stone as aggregate and white cement as cementitious material, but the white cement-based permeable bricks have the disadvantages of large permeability coefficient and low compressive strength. Such white cement-based permeable bricks that rely on large pores between particles are easily blocked by debris such as mud and sand, and have poor permeability. Therefore, how to avoid this phenomenon is the key to solving the problem. For example, patent CN200780039199.7 discloses composite permeable bricks and mixtures for making the surface layer of composite permeable bricks. The composite permeable bricks and mixtures of the present invention can be used for road paving, water circulation, water filtration and water purification, but their flexural strength is poor. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] In view of the deficiencies in the prior art, the present invention provides a microcrystalline bead high-efficiency water-permeable composite brick and a preparation method thereof, which has good compression resistance and will not turn white due to alkali.
[0005] (II) Technical solution
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a microcrystalline bead high-efficiency water-permeable composite brick, comprising a base layer and a surface layer, the base layer comprising 140-170 parts by weight of ceramic shale particles, 120-130 parts by weight of ceramic fine powder, 280-320 parts by weight of white cement, 0.8-1 parts by weight of a reinforcing agent, and 120-150 parts by weight of water; the surface layer comprises 500-600 parts by weight of natural colored sand, 10-15 parts by weight of modified polyurethane, 4-7 parts by weight of epoxy nano-silica, 90-130 parts by weight of quartz powder, and 1-2 parts by weight of a polycarboxylic acid water reducer.
[0007] Preferably, the preparation method of the modified polyurethane in the surface layer is:
[0008] (1) Add 1,3-adamantanediol and propyl caprolactone to N,N-dimethylformamide solvent, mix well, add stannous octoate catalyst, react at 60-70° C. for 6-10 h, and after the reaction, distill under reduced pressure, wash, and dry to obtain intermediate 1;
[0009] (2) In a nitrogen atmosphere, 1,1-bis(dimethylsilyl) iron and propenyl-1,3-sultone are added to a reaction kettle containing an acetonitrile solvent, stirred evenly, and chloroplatinic acid catalyst is added thereto, reacted at 65-80° C. for 45-60 minutes, and then cooled to room temperature to obtain ferrocene-modified sultone;
[0010] (3) adding 8-12 parts by weight of 4,6-diamino-2-hydroxy-1,3,5-triazine and 6-15 parts by weight of ferrocene-modified sultone to N,N-dimethylformamide solvent, stirring evenly, adding sodium hydroxide, reacting at 65-80° C. for 7-15 hours, and then rotary distilling, filtering and drying to obtain a sodium sulfonate chain extender;
[0011] (4) Toluene diisocyanate and polyether polyol are added to a reactor, and then dibutyltin dilaurate catalyst is added to carry out prepolymerization under a nitrogen atmosphere at a temperature of 70-90° C. for 2-4 h. Then, intermediate 1 is added and stirred for 20-30 min. Then, sodium sulfonate chain extender is added and reacted at 60-70° C. for 40-60 min. After the reaction is completed, the mixture is naturally cooled and discharged to obtain a modified polyurethane.
[0012] Preferably, the mass ratio of 1,3-adamantanediol, propyl caprolactone and stannous octoate catalyst in (1) is 1.2-1.4:1:0.02-0.03.
[0013] Preferably, the mass ratio of 1,1-bis(dimethylsilyl)iron, propenyl-1,3-sultone and chloroplatinic acid catalyst in (2) is 1:0.9-1.4:0.03-0.05.
[0014] Preferably, the mass fraction of sodium hydroxide in (3) is 12-14%.
[0015] Preferably, the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate catalyst, intermediate 1, and sodium sulfonate chain extender in (4) is 1:1.2-1.3:0.04-0.06:0.6-0.9:0.5-0.8.
[0016] Preferably, the preparation method of the microcrystalline bead high-efficiency water-permeable composite brick is:
[0017] S1. Add ceramic shale particles, ceramic fine powder, white cement, reinforcing agent and water into a mixer, stir for 10-30s, discharge the material and obtain a base layer;
[0018] S2. Add natural colored sand, modified polyurethane, epoxy nano-silica, quartz powder, and polycarboxylic acid water reducer into a mixer, stir for 15-35 seconds, and evenly spread on the base layer for extrusion molding.
[0019] (III) Beneficial technical effects
[0020] The invention provides a base layer by adding ceramic shale particles, ceramic fine powder, white cement, a reinforcing agent and water into a stirrer, stirring and discharging the mixture; and adding natural colored sand, modified polyurethane, epoxy nano-silica, quartz powder and polycarboxylic acid water reducing agent into the stirrer, stirring and evenly spreading the mixture on the base layer for extrusion molding.
[0021] The hydroxyl group in 1,3-adamantanediol and propyl caprolactone are reacted to obtain intermediate 1, the silicon-hydrogen bond in 1,1-di(dimethylsilyl)iron and the alkenyl group in propenyl-1,3-sultone are subjected to addition reaction to obtain ferrocene-modified sultone, 4,6-diamino-2-hydroxy-1,3,5-triazine and ferrocene-modified sultone are reacted to obtain sodium sulfonate chain extender, toluene diisocyanate and polyether polyol are added to a reactor, dibutyltin dilaurate catalyst is added to perform prepolymerization, intermediate 1 is added to perform reaction by stirring, and then sodium sulfonate chain extender is continuously added to perform reaction to obtain modified polyurethane.
[0022] During the stirring process, the terminal hydroxyl groups in the modified polyurethane will react with the epoxy groups in the epoxy nano-silica to produce a ring-opening reaction, which increases the compatibility between each other and makes it more evenly dispersed in the composite brick; the adamantane structure in the modified polyurethane has good stability, which improves the mechanical properties of the composite brick. The ferrocene group therein improves the durability of the composite brick. The polyurethane itself can also improve the durability and compressive resistance of the composite brick. The sulfonic acid group therein will form a water-reducing agent system together with the polycarboxylic acid water-reducing agent to improve the strength of the composite brick. DETAILED DESCRIPTION
[0023] Example 1
[0024] (1) Add 1,3-adamantanediol and propyl hexyl lactone to N,N-dimethylformamide solvent, mix well, add stannous octoate catalyst, wherein the mass ratio of 1,3-adamantanediol, propyl hexyl lactone and stannous octoate catalyst is 1.2:1:0.02, react at 60° C. for 6 h, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;
[0025] (2) In a nitrogen atmosphere, 1,1-bis(dimethylsilyl) iron and propenyl-1,3-sultone were added to a reaction kettle containing an acetonitrile solvent, and the mixture was stirred evenly. A chloroplatinic acid catalyst was added thereto, wherein the mass ratio of 1,1-bis(dimethylsilyl) iron, propenyl-1,3-sultone, and chloroplatinic acid catalyst was 1:0.9:0.03, and the mixture was reacted at 65° C. for 45 minutes. After the reaction was completed, the mixture was cooled to room temperature to obtain ferrocene-modified sultone;
[0026] (3) adding 8 parts by weight of 4,6-diamino-2-hydroxy-1,3,5-triazine and 6 parts by weight of ferrocene-modified sultone to N,N-dimethylformamide solvent, stirring evenly, adding 12% by weight of sodium hydroxide, reacting at 65° C. for 7 h, and then performing rotary distillation, filtering and drying to obtain a sodium sulfonate chain extender;
[0027] (4) adding toluene diisocyanate and polyether polyol into a reaction kettle, and then adding dibutyltin dilaurate catalyst, and prepolymerizing under nitrogen atmosphere, the prepolymerization temperature is 70°C, the time is 2h, and then adding intermediate 1, stirring for 20min, and then continuing to add sodium sulfonate chain extender, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate catalyst, intermediate 1, and sodium sulfonate chain extender is 1:1.2:0.04:0.6:0.5, reacting at 60°C for 40min, after the reaction is completed, naturally cooling, discharging, and obtaining modified polyurethane;
[0028] (5) adding 140 parts by weight of ceramic shale particles, 120 parts by weight of ceramic fine powder, 280 parts by weight of white cement, 0.8 parts by weight of reinforcing agent, and 120 parts by weight of water into a stirrer, stirring for 10 seconds, and discharging to obtain a base layer;
[0029] (6) Add 500 parts by weight of natural colored sand, 10 parts by weight of modified polyurethane, 4 parts by weight of epoxy nano-silica, 90 parts by weight of quartz powder, and 1 part by weight of polycarboxylic acid water reducer into a stirrer, stir for 15 seconds, and evenly spread on the base layer for extrusion molding.
[0030] Example 2
[0031] (1) Add 1,3-adamantanediol and propyl hexyl lactone to N,N-dimethylformamide solvent, mix well, add stannous octoate catalyst, wherein the mass ratio of 1,3-adamantanediol, propyl hexyl lactone and stannous octoate catalyst is 1.4:1:0.03, react at 70° C. for 10 h, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;
[0032] (2) In a nitrogen atmosphere, 1,1-bis(dimethylsilyl) iron and propenyl-1,3-sultone were added to a reaction kettle containing an acetonitrile solvent, and the mixture was stirred evenly. A chloroplatinic acid catalyst was added thereto, wherein the mass ratio of 1,1-bis(dimethylsilyl) iron, propenyl-1,3-sultone, and chloroplatinic acid catalyst was 1:1.4:0.05, and the mixture was reacted at 80° C. for 60 min. After the reaction was completed, the mixture was cooled to room temperature to obtain ferrocene-modified sultone;
[0033] (3) adding 12 parts by weight of 4,6-diamino-2-hydroxy-1,3,5-triazine and 15 parts by weight of ferrocene-modified sultone to N,N-dimethylformamide solvent, stirring evenly, adding 14% by weight of sodium hydroxide, reacting at 80° C. for 15 h, and then rotary distilling, filtering and drying to obtain a sodium sulfonate chain extender;
[0034] (4) Adding toluene diisocyanate and polyether polyol into a reactor, adding dibutyltin dilaurate catalyst, and prepolymerizing under a nitrogen atmosphere at a temperature of 90° C. for 4 hours, then adding intermediate 1, stirring for 30 minutes, and then continuing to add sodium sulfonate chain extender, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate catalyst, intermediate 1, and sodium sulfonate chain extender is 1:1.3:0.06:0.9:0.8, reacting at 70° C. for 60 minutes, and after the reaction is completed, naturally cooling and discharging to obtain a modified polyurethane;
[0035] (5) adding 170 parts by weight of ceramic shale particles, 130 parts by weight of ceramic fine powder, 320 parts by weight of white cement, 1 part by weight of reinforcing agent, and 150 parts by weight of water into a stirrer, stirring for 30 seconds, and discharging to obtain a base layer;
[0036] (6) 600 parts by weight of natural colored sand, 15 parts by weight of modified polyurethane, 7 parts by weight of epoxy nano-silica, 130 parts by weight of quartz powder, and 2 parts by weight of polycarboxylic acid water reducer were added into a stirrer, stirred for 35 seconds, and evenly spread on the base layer for extrusion molding.
[0037] Example 3
[0038] (1) Add 1,3-adamantanediol and propyl hexanoate to N,N-dimethylformamide solvent, mix well, add stannous octoate catalyst, wherein the mass ratio of 1,3-adamantanediol, propyl hexanoate and stannous octoate catalyst is 1.3:1:0.025, react at 65°C for 8h, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;
[0039] (2) In a nitrogen atmosphere, 1,1-bis(dimethylsilyl) iron and propenyl-1,3-sultone were added to a reaction kettle containing an acetonitrile solvent, and the mixture was stirred evenly. A chloroplatinic acid catalyst was added thereto, wherein the mass ratio of 1,1-bis(dimethylsilyl) iron, propenyl-1,3-sultone, and chloroplatinic acid catalyst was 1:1.15:0.04, and the mixture was reacted at 72° C. for 52.5 min. After the reaction was completed, the mixture was cooled to room temperature to obtain ferrocene-modified sultone;
[0040] (3) adding 10 parts by weight of 4,6-diamino-2-hydroxy-1,3,5-triazine and 10.5 parts by weight of ferrocene-modified sultone to N,N-dimethylformamide solvent, stirring evenly, adding 13% by weight of sodium hydroxide, reacting at 72° C. for 11 hours, and then performing rotary distillation, filtering and drying to obtain a sodium sulfonate chain extender;
[0041] (4) adding toluene diisocyanate and polyether polyol into a reaction kettle, and then adding dibutyltin dilaurate catalyst, and prepolymerizing under a nitrogen atmosphere, the prepolymerization temperature is 80°C, the time is 3h, and then adding intermediate 1, stirring for 25min, and then continuing to add sodium sulfonate chain extender, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate catalyst, intermediate 1, and sodium sulfonate chain extender is 1:1.25:0.05:0.75:0.65, reacting at 65°C for 50min, after the reaction is completed, naturally cooling, discharging, and obtaining a modified polyurethane;
[0042] (5) adding 155 parts by weight of ceramic shale particles, 125 parts by weight of ceramic fine powder, 300 parts by weight of white cement, 0.9 parts by weight of reinforcing agent, and 135 parts by weight of water into a stirrer, stirring for 20 seconds, and discharging to obtain a base layer;
[0043] (6) 550 parts by weight of natural colored sand, 12.5 parts by weight of modified polyurethane, 5.5 parts by weight of epoxy nano-silica, 110 parts by weight of quartz powder, and 1.5 parts by weight of polycarboxylic acid water reducer were added into a stirrer, stirred for 25 seconds, and evenly spread on the base layer for extrusion molding.
[0044] Example 4
[0045] (1) Add 1,3-adamantanediol and propyl hexyl lactone to N,N-dimethylformamide solvent, mix well, add stannous octoate catalyst, wherein the mass ratio of 1,3-adamantanediol, propyl hexyl lactone and stannous octoate catalyst is 1.2:1:0.02, react at 60° C. for 6 h, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;
[0046] (2) In a nitrogen atmosphere, 1,1-bis(dimethylsilyl) iron and propenyl-1,3-sultone were added to a reaction kettle containing an acetonitrile solvent, and the mixture was stirred evenly. A chloroplatinic acid catalyst was added thereto, wherein the mass ratio of 1,1-bis(dimethylsilyl) iron, propenyl-1,3-sultone, and chloroplatinic acid catalyst was 1:0.9:0.03, and the mixture was reacted at 65° C. for 45 minutes. After the reaction was completed, the mixture was cooled to room temperature to obtain ferrocene-modified sultone;
[0047] (3) adding 12 parts by weight of 4,6-diamino-2-hydroxy-1,3,5-triazine and 15 parts by weight of ferrocene-modified sultone to N,N-dimethylformamide solvent, stirring evenly, adding 14% by weight of sodium hydroxide, reacting at 80° C. for 15 h, and then rotary distilling, filtering and drying to obtain a sodium sulfonate chain extender;
[0048] (4) Adding toluene diisocyanate and polyether polyol into a reactor, adding dibutyltin dilaurate catalyst, and prepolymerizing under a nitrogen atmosphere at a temperature of 90° C. for 4 hours, then adding intermediate 1, stirring for 30 minutes, and then continuing to add sodium sulfonate chain extender, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate catalyst, intermediate 1, and sodium sulfonate chain extender is 1:1.3:0.06:0.9:0.8, reacting at 70° C. for 60 minutes, and after the reaction is completed, naturally cooling and discharging to obtain a modified polyurethane;
[0049] (5) adding 155 parts by weight of ceramic shale particles, 125 parts by weight of ceramic fine powder, 300 parts by weight of white cement, 0.9 parts by weight of reinforcing agent, and 135 parts by weight of water into a stirrer, stirring for 20 seconds, and discharging to obtain a base layer;
[0050] (6) 550 parts by weight of natural colored sand, 12.5 parts by weight of modified polyurethane, 5.5 parts by weight of epoxy nano-silica, 110 parts by weight of quartz powder, and 1.5 parts by weight of polycarboxylic acid water reducer were added into a stirrer, stirred for 25 seconds, and evenly spread on the base layer for extrusion molding.
[0051] Comparative Example 1
[0052] The difference between this comparative example and Example 4 is that no modified polyurethane is added.
[0053] The water-permeable composite bricks prepared in Examples 1-4 and Comparative Example 1 were taken to measure their water permeability coefficient, single brick weight and compressive strength, and the results of alkali whitening after 2 years of use are shown in Table 1 below.
[0054] Table 1: Composite brick performance test.
[0055]
[0056] As can be seen from Table 1, the composite materials obtained in Examples 1-4 of the present invention have better compression and flexural resistance than those in Comparative Example 1, and will not turn white due to alkali.
[0057] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Microcrystalline bead high-efficiency water-permeable composite brick, characterized by: The invention comprises a base layer and a surface layer, wherein the base layer comprises 140-170 parts by weight of ceramic shale particles, 120-130 parts by weight of ceramic fine powder, 280-320 parts by weight of white cement, 0.8-1 parts by weight of a reinforcing agent, and 120-150 parts by weight of water; and the surface layer comprises 500-600 parts by weight of natural colored sand, 10-15 parts by weight of modified polyurethane, 4-7 parts by weight of epoxy nano-silica, 90-130 parts by weight of quartz powder, and 1-2 parts by weight of a polycarboxylic acid water reducer.
2. The microcrystalline bead high-efficiency water-permeable composite brick according to claim 1 is characterized in that: The preparation method of the modified polyurethane in the surface layer is: (1) Add 1,3-adamantanediol and propyl caprolactone to N,N-dimethylformamide solvent, mix well, add stannous octoate catalyst, react at 60-70° C. for 6-10 h, and after the reaction, distill under reduced pressure, wash, and dry to obtain intermediate 1; (2) In a nitrogen atmosphere, 1,1-bis(dimethylsilyl) iron and propenyl-1,3-sultone are added to a reaction kettle containing an acetonitrile solvent, stirred evenly, and chloroplatinic acid catalyst is added thereto, reacted at 65-80° C. for 45-60 minutes, and then cooled to room temperature to obtain ferrocene-modified sultone; (3) adding 8-12 parts by weight of 4,6-diamino-2-hydroxy-1,3,5-triazine and 6-15 parts by weight of ferrocene-modified sultone to N,N-dimethylformamide solvent, stirring evenly, adding sodium hydroxide, reacting at 65-80° C. for 7-15 hours, and then rotary distilling, filtering and drying to obtain a sodium sulfonate chain extender; (4) Toluene diisocyanate and polyether polyol are added to a reactor, and then dibutyltin dilaurate catalyst is added to carry out prepolymerization under a nitrogen atmosphere at a temperature of 70-90° C. for 2-4 h. Then, intermediate 1 is added and stirred for 20-30 min. Then, sodium sulfonate chain extender is added and reacted at 60-70° C. for 40-60 min. After the reaction is completed, the mixture is naturally cooled and discharged to obtain a modified polyurethane.
3. The microcrystalline bead high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass ratio of 1,3-adamantanediol, propyl caprolactone and stannous octoate catalyst in (1) is 1.2-1.4:1:0.02-0.
03.
4. The microcrystalline bead high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass ratio of 1,1-bis(dimethylsilyl)iron, propenyl-1,3-sultone and chloroplatinic acid catalyst in (2) is 1:0.9-1.4:0.03-0.
05.
5. The microcrystalline bead high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass fraction of sodium hydroxide in (3) is 12-14%.
6. The microcrystalline bead high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate catalyst, intermediate 1 and sodium sulfonate chain extender in (4) is 1:1.2-1.3:0.04-0.06:0.6-0.9:0.5-0.
8.
7. A method for preparing a microcrystalline bead high-efficiency water-permeable composite brick according to any one of claims 1 to 6, characterized in that: The preparation method of the microcrystalline bead high-efficiency water-permeable composite brick is as follows: S1. Add ceramic shale particles, ceramic fine powder, white cement, reinforcing agent and water into a stirrer, stir for 10-30s, discharge the material and obtain a base layer; S2. Add natural colored sand, modified polyurethane, epoxy nano-silica, quartz powder, and polycarboxylic acid water reducer into a mixer, stir for 15-35 seconds, and evenly spread on the base layer for extrusion molding.
Citation Information
Cited By
High-wear-resistance polyurethane packaging material for electronic products and preparation method of high-wear-resistance polyurethane packaging material
CN119798961A
High abrasion resistant polyurethane packaging material for electronic products and method for preparing the same
CN119798961B
